Evaluation Research on Lecturers’ Pedagogical Competence of UIA - Fajaria, Nurul Hasanah; Budiningsih, Iffah; A’yun, Qurrota; Fahrudin, Muhammad (RSF Conference Series: Business, Management and Social Sciences, 2023)
It is believed that lecturers contribute a significant effect on the quality of graduates. This research aims to evaluate lecturers’ pedagogical competence at UIA and to provide recommendations for improvement. This is a survey study design, where the target population is all students at UIA Jakarta, with the limited population is the sixth-semester of undergraduate students. The sampling method used simple random sampling. The data are gathered through a questionnaire and analyzed using descriptive statistics. The result shows that the average score of lecturers’ pedagogical competence is 3.51 (good), with the highest score 3.63 is, beginning and ending the lesson with a greeting and prayer. Pedagogical competence is important in bridging the gap in learning achievement. Technological Pedagogical Content Knowledge (TPACK) is a learning model that integrates technological knowledge into content and pedagogical concepts. TPACK model has become a lecturer’s need in dealing with education trends in the digital era, which is highly dependent on integrating technology in the teaching and learning process. The recommendations as the implication of the study are encouraging UIA lecturers to participate in Instructional Techniques Training (PEKERTI) for professional certification, implementing the TPACK model in their teaching, and ensuring adequate access and quality of ICT facilities to support academic activities on campus.